2020
DOI: 10.17275/per.20.44.7.3
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Effect of Reading Comprehension in the Relationship between Logical Reasoning and Word Problem Solving

Abstract: Reading comprehension skill is seen as a predictor of word problemsolving performance, and the close relationship between reading comprehension and mathematical skills is accentuated. On the other hand, more research is needed as to determine how logical thinking and word problem solving are related to each other and to analyze the role of reading comprehension in this relationship. The aim of the study is to examine the role of reading comprehension in the relation between logical reasoning and word problem-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These results are not surprising since one of the most important phases of problem-solving understanding the problem (Lau, It is the most important action for students to attempt to comprehend the problem since it is unlikely that a problem can be solved without comprehending it (Ozturk et al, 2020). Previous research has also shown that even mathematically strong children have difficulty solving problems owing to an incorrect comprehending of the problem situation or limited reading comprehension skills (e.g., Bjork & Crane, 2013;Boonen et al, 2014;Özcan & Doğan, 2018;Can, 2020). Moreover, most previous studies indicate that reading comprehension has a stronger impact on problem-solving than arithmetic skills, logical reasoning, and spatial skills (e.g., Lee et al, 2004;Hart et al, 2010;Bjork & Crane, 2013;Harlaar et al, 2012;Fuchs et al, 2015;Murrihy et al, 2017;Pongsakdi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are not surprising since one of the most important phases of problem-solving understanding the problem (Lau, It is the most important action for students to attempt to comprehend the problem since it is unlikely that a problem can be solved without comprehending it (Ozturk et al, 2020). Previous research has also shown that even mathematically strong children have difficulty solving problems owing to an incorrect comprehending of the problem situation or limited reading comprehension skills (e.g., Bjork & Crane, 2013;Boonen et al, 2014;Özcan & Doğan, 2018;Can, 2020). Moreover, most previous studies indicate that reading comprehension has a stronger impact on problem-solving than arithmetic skills, logical reasoning, and spatial skills (e.g., Lee et al, 2004;Hart et al, 2010;Bjork & Crane, 2013;Harlaar et al, 2012;Fuchs et al, 2015;Murrihy et al, 2017;Pongsakdi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a greater relationship between reading comprehension and problem-solving (r = .45) than arithmetic skills (r = .42) and spatial skills (r = .34) among elementary students is reported by Murrihy et al (2017). Likewise, a strong relationship (r = .60) between problem-solving and reading comprehension and a moderate relationship (r = .49) between reading comprehension and logical reasoning among elementary students are found by Can (2020). However, some studies (e.g., Swanson, 2004;Bullen et al, 2020) show that there is a greater relationship between reading comprehension and arithmetic skills than problem-solving.…”
Section: Potential Moderators In the Context Of Mathematics Skills An...mentioning
confidence: 93%
See 1 more Smart Citation
“…The positive correlation between word problem solving and logical reasoning skills suggests that activities to improve word problemsolving performance should be supported by logical reasoning-and inference making-related activities. The fact that reading comprehension skills play a mediating role between these two performances reveals the importance of linguistic skills such as reading comprehension in the development of logical and mathematical thinking (Can, 2020).…”
Section: Previous Related Researchmentioning
confidence: 99%
“…Referring to various English tests, reading comprehension is part of TOEFL, IELTS and TOEIC, which are considered as well-known proficiency tests. Reading comprehension skill is viewed as a predictor of word problem solving performance, and the close relationship between reading comprehension and mathematical skills is accentuated (Can, 2020). Therefore, the researchers were interested in analysing reading comprehension through the available stories in the parenting-themed coloring book.…”
Section: Introductionmentioning
confidence: 99%